Kinetics of the thermal degradation of lycopene in tomatoes - Aliyu, Adamu (Array, 2020)
This research studied the kinetics of the thermal degradation of lycopene in tomatoes using elevated temperature testing. Understanding the nature and the extent of sensitive nutrient degradation in tomatoes will assist in reducing postharvest nutrient losses during storage and processing. Ripe tomatoes were sorted, washed, and blinded. Juice was obtained by filtering the blinded pulp through a muslin cloth. The samples were heated using a water bath at 70, 80, 90, and 100 °C for 20, 40, 60, and 80 minutes. The determination of lycopene was done using spectrophotometric methods at 503 nm, in hexane: ethanol: acetone (2:1:1 v/v/v) lycopene extract. The concentrations of lycopene were determined immediately after processing. The data was found to fit into first order equations. Degradation constants (k), D-value, and half-life for the thermal degradation of lycopene were determined at each processing temperature. Models were also developed for each of the chosen temperatures, which can be used to predict the degradation pattern of lycopene at other processing conditions. Z-value, Q10, and activation energy for the degradation of lycopene were also determined. Analyses showed a considerable decrease in lycopene concentration and decimal reduction time (D-value), and a significant increase in the thermal degradation rate (k) during heating from 70 to 100 °C. The finding shows that the degradation of lycopene in tomatoes followed the first order kinetics and it shows that the lycopene content decreased at 80 to 100 °C.